A case report of left ovarian borderline mucinous cystadenomatous cyst containing a neural sarcomatous nodule in an 18 year old female - Abulhassan, Nashwa; Miskry, Tariq; El Mouslemany, Mohamed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
This is a unique case of a 13 cm torted ovarian borderline mucinous cystadenoma with a neural sarcomatous nodule in an 18 year old female. No previous similar cases have been reported in the literature. There are 6 reported cases of pure ovarian osteosarcoma, 5 cases of osteosarcoma arising from an ovarian teratoma, and 2 cases of osteosarcomas of osseous origin (humerus and maxilla) with metastasis to the ovary in the English literature. An 18 year old female presented with a sudden onset of left flank pain radiating to the left loin. She was not examined vaginally as was never sexually active. TA/US showed normal abdomen, a large complex pelvic cyst 107 mm x 100 75 mm possibly a left dermoid ovarian cyst. CA125, alpha feto- protein and beta HCG were requested and were awaited. Physical examination showed mild tenderness in the left iliac fossa and suprapubically. There was neither guarding nor rigidity. The diagnosis was a torted ovarian cyst and an emergency laparoscopic procedure to investigate the pain was performed. A torted left ovarian cyst occupying the pelvis and upper abdomen 13 cm x 13 cm in size was found. Left ovary was untorted and an ovarian cystectomy was performed. Intraperitoneal Cystic fluid spillage occurred during retrieval of cyst through the endobag. Peritoneal lavage with 300 ml of fluid was carried out at the end of the procedure. Histology report from the cyst showed a neural nodule which appears to be an osteosarcoma arising in a background of a borderline mucinous ovarian tumour. Following an MDT discussion, she had a laparoscopic left salpingo-oophorectomy with peritoneal washings and omental biopsy. Peritoneal washings did not show malignant cells. Histology report has confirmed absence of residual ovarian tumour and absence of omental deposits. The prognosis of the borderline mucinous tumours is vastly superior to that of a cystadenocarcinoma. Preserving the contralateral uninvolved ovary in a young woman with a borderline mucinous ovarian tumour is the current trend of management; however the prognosis of borderline ovarian mucinous cystadenomas is less certain in the presence of sarcomatous changes. Ovarian osteosarcomas are rare malignancies that commonly occur in old age group. Most patients have advanced stage disease at presentation.